“Optimisme kosong dalam Kehidupan Manusia:”suatu Konsep Hebel dalam kitab Pengkhotbah 1:2-11” - Edward Sahat Bintang Silalahi; Farel Yosua Sualang (Jurnal Kala Nea, 2025)
This article employs a thematic analysis of Ecclesiastes 1:2–11 to elucidate the theological function of the phrase hebel as the conceptual framework of the book. A review of the extant literature reveals a general tendency among previous studies to emphasize the theme of the meaning of life in a broad sense or the book as a whole. Consequently, the prologue section has rarely been examined through thematic exegesis. Furthermore, previous studies have emphasized lexical analysis of hebel without relating it to the thematic structure of verses 2–11, so that the relationship between the verses and their contribution to the book's theological creed has not been fully explored. The passage is divided into five units by the study: hebel as a creed (verse 2), the limitations of human endeavor (verse 3), the cycle of the cosmos and transience (verses 4–7), existential weariness (verses 8–10), and historical oblivion (verse 11). The findings of the analysis demonstrate a progressive argument that affirms human limitations while criticizing empty optimism in life. This study makes a significant contribution to the field of wisdom theology by affirming that the passage under scrutiny serves to fortify the book's confrontational theological foundation. Moreover, it calls upon readers to adopt a God-centered orientation in life.